IMPLEMENTION OF MASTERY LEARNING STRATEGY TO IMPROVE STUDENT LEARNING OUTCOMES IN THE BASIC OF PHYSICS II - Azizahwati Azizahwati; Sugoro Bhakti Sutono; Salman Alfarisi (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
This research aims to describe the learning outcomes of basic physics learning II students Industrial Engineering of Pelalawan Institute of Technologyon the concept of electricity. The subject of this research is the second semester students of Industrial Engineering of Pelalawan Institute of Technology. The instrument used for data collection is the learning outcomes test given after the application of mastery learning strategy. Data were analyzed using descriptive analysis technique covering the students' learning achievement. The results of data analysis showed student learning outcomes categorized average. Application of strategy Mastery learning can improve student's basic physics learning outcomes on electrical materials.